Sexual activity and protection of reproductive health among female students - Bošnjak, Kristina Z; Rakić, Dušica (Medicinski podmladak, 2020)
Introduction: Early sexarha and multiple sex partners are leading risk factors for the development of sexual transmitted diseases and cervical cancer. Raising the level of knowledge about measures to protect reproductive health among young people can lead to significant reduction of same. Material and methods: The survey was conducted among 269 female students, on Faculty of Philosophy, Faculty of Agriculture and Faculty of Medicine, on the University of Novi Sad (age 19-24 years), at the beginning of 2019. year. Anonymus qestionnaire was used as the instrument for the research. Statistical analysis was carried out in SPSS Statistics 20. Results: Early sexual activity, before 18 years had 33.7% of respondents (average age 16.44). 32% students had one, and 13.4% had 4 sexual partners or more. Condom use 62.2% of studens, but 8% of women don't use any protection. One-third of a students knows that HPV infection can cause cervical cancer, 60.6% didn't heard for a vaccine against HPV. There is a statistically significant difference in knowledge about reproductive health and in terms of contraceptive methods between a medical female students and female students on other faculties. Conclusion: There is significant percentage of female students who had wound sexarha and low  knowledge about reproductive health. This points to the need for more intense sex education in order to raise the level of knowledge about measures to protect reproductive health. Keywords: sexual activity; reproductive health; HPV; female students